DESIGN OF THE REBUILDING THE ONE-AXLE WORKING MACHINE TO TWO-AXLE WORKING MACHIN (Perner's Contacts, 2017)
This article deals with the design of the rebuilding the working machine with one axle to the working machine with two axles. Obtained visualised designs will provide the overview on the machine state after real prototype construction. The improvement of the driving and operational properties of the machine is the goal of this rebuilding and also its applicability will be increased. The design will incline to these basic criteria: retention of compact dimensions in order to transport it on a trailer for a car, easy machine handling and attendance and also passability. The aim is that dimensions of the the new machine design will provide the sufficient space for the ergonomic layout of the operator’s position along with the retention of the gross machine weight up to 500 kg by reason of the load capacity of the standard trailer for a car.
Keywords: working machine; additional axle; engineering design